COMPARATIVE ANALYSIS OF FIGURATIVE EXPRESSIONS IN ENGLISH AND UZBEK LANGUAGES (BASED ON TROPES) - Shukurova Pokiza (Western European Studies, 2025)
This article conducts an in-depth comparative analysis of figurative expressions, focusing specifically on tropes in English and Uzbek languages. It explores the intricate functioning of metaphors, metonymies, hyperboles, similes, and synecdoches, while investigating their linguistic structures, cognitive significance, and cultural peculiarities. The study reveals both universal features and culture-specific variations in the usage of figurative language, emphasizing the role of tropes in reflecting worldviews and shaping intercultural understanding
Keywords: Figurative expressions; trope; metaphor